Will artificial intelligence replace the work of live designers? - Dovgal, A. (Universidad de Guanajuato Primera Edición, 2024)
Artificial intelligence is increasingly becoming an integral part of the lives of modern designers. Currently, with the help of artificial intelligence, it is pos-sible to significantly simplify and reduce the time spent on routine design processes such as overall process organization, photo retouching, color pal-ette selection, applying styles and filters, layout, creating icons, and simple illustrations. More experienced users can create high-quality images.
Keywords: artificial intelligence; design processes